Organic metal complex as well as preparation method and application thereof
By adding organometallic complexes (such as TTz-Pt) to the active layer of organic solar cells, the problem of insufficient exciton diffusion length is solved, the power conversion efficiency and performance of the device are significantly improved, and the commercialization of organic solar cells is promoted. process.
Patent Information
- Application Number
- CN202411586200.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The prior art is difficult to effectively improve the exciton diffusion length and device parameters of organic solar cells, which limits the performance and commercialization process of thick-film organic solar cells.
Develop an organic metal complex (such as TTz-Pt) through which it is added as a solid additive to the active layer of an organic solar cell to improve material crystallinity, reduce trap density, and regulate exciton diffusion behavior.
The power conversion efficiency of organic solar cells is significantly improved, especially at a thickness of 300 nanometers, the conversion efficiency reaches 18.84%, and the exciton diffusion length is extended, promoting the efficient performance of the device.
Smart Images

Figure CN119462772A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymer photovoltaic devices, in particular to an organic metal complex and a preparation method and application thereof. Background Art
[0002] Organic solar cells (OSCs) have attracted attention as a clean and renewable energy technology due to their inherent flexibility, cost-effectiveness, and solution processability. With advances in material design (donor and acceptor materials) and device engineering, power conversion efficiencies (PCEs) of 20% have been achieved in single-junction OSCs. However, despite the high efficiency achieved in thin-film organic solar cells, increasing the thickness of the active layer usually degrades the device performance and is not conducive to large-scale production. To achieve the commercialization of organic solar cells, it is necessary to develop efficient thick-film organic solar cells with a thickness of several hundred nanometers to enhance photon absorption and promote more excitons to diffuse to the D / A interface. However, the short exciton diffusion length, space charge accumulation, and severe charge carrier recombination of organic materials significantly limit the device parameters of thick-film organic solar cells.
[0003] Exciton diffusion is a key parameter affecting the photovoltaic performance of thick-film organic solar cells. The probability of exciton diffusion to the D / A interface depends on the exciton diffusion length, which is positively correlated with the exciton diffusion coefficient (D) and the exciton lifetime (τ). Previous studies have shown that improving material crystallinity, reducing energy disorder, and reducing trap density effectively enhance the exciton diffusion coefficient, thereby further increasing the exciton diffusion length. In addition, synthesizing new photovoltaic materials is an effective strategy to extend the exciton lifetime and thus the exciton diffusion length, but the synthesis of new photovoltaic materials increases the complexity and cost of the synthesis. Therefore, there is an urgent need to develop a simple and effective method that can simultaneously improve material crystallinity, reduce trap density, regulate exciton diffusion behavior, and optimize morphology. Summary of the invention
[0004] In order to overcome the above problems existing in the prior art, the present invention provides an organic metal complex and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention to solve the technical problem is: an organic metal complex, the structural formula of the organic metal complex is: .
[0006] Wherein, the metal X is selected from any one of Pt, Pd, Cu, Fe, Ni, Co, and Zn; The R unit is selected from any one of a linear or branched alkyl group having 1 to 3 carbon atoms.
[0007] The method for preparing an organic metal complex is characterized in that it is used to prepare the organic metal complex as described above, and specifically comprises: Step 1, under nitrogen protection, 2-bromothiazole, 2-(tributyltinyl)thiophene or (thieno[3,2-b]thiophene-2-yl)tributyltin and a catalytic amount of tetrakistriphenylphosphine palladium are added to a flask; anhydrous toluene is added, and the reaction mixture is stirred at 110° C. for 24 hours; after cooling, the mixture is poured into ultrapure water and extracted with dichloromethane; the organic layer is dried over anhydrous MgSO4; the solvent is removed by evaporation under reduced pressure, and the crude product is purified by silica gel column chromatography to obtain compound 2-(thiophene-2-yl)thiazole or 2-(thieno[3,2-b]thiophene-2-yl)thiazole; Step 2, adding an aqueous solution of K2XCl4 to the acetic acid solution of 2-(thiophene-2-yl)thiazole or 2-(thieno[3,2-b]thiophene-2-yl)thiazole obtained in step 1, and reflux heating under nitrogen; filtering to obtain a dimer, washing with acetic acid and ethanol, and vacuum drying; reflux heating the dimer and sodium acetylacetonate in acetone, removing the solvent under reduced pressure, and purifying the complex by silica gel chromatography to obtain an organic metal complex.
[0008] An application of the above-mentioned organometallic complex in the preparation of thick-film organic solar cells.
[0009] Preferably, the specific preparation method of the thick film organic solar cell includes: Step 1, the ITO-coated glass substrate is cleaned by ultrasonic in detergent, deionized water, acetone and isopropanol, and blown dry with nitrogen; Step 2, treating the glass substrate obtained in step 1 with oxygen plasma, spin-coating PEDOT:PSS on the glass substrate, and transferring the substrate to a glove box filled with nitrogen after drying; Step 3, spin coating an active layer with an organic metal complex on the substrate obtained in step 2, and performing a thermal annealing treatment; Step 4: Spin-coat the PDINN solution on the substrate obtained in step 3, and form a top electrode by evaporating 100 nanometers of Ag.
[0010] Preferably, the amount of the organic metal complex added in step 3 is 1.5%-4.5% of the weight of the feedstock.
[0011] Preferably, the active layer is one of D18-Cl:L8-BO, PM6:L8-BO, and D18:L8-BO:IDIC.
[0012] Preferably, the active layer has a thickness of 100-300 nanometers.
[0013] The beneficial effect of the present invention is that the present invention synthesizes an organic metal complex based on 2-(thiophene-2-yl)thiazole and adds it to the active layer of an organic solar cell as a new solid additive. The power conversion efficiency of the organic solar cell with the additive is significantly improved, and when the thickness of the active layer reaches 300 nanometers, the power conversion efficiency is still relatively high, especially the TTz-Pt additive has a particularly significant effect, and the conversion efficiency can reach 18.84% when the thickness of the active layer reaches 300 nanometers. The present invention proposes a simple and effective method to effectively extend the exciton diffusion length, realize the preparation of high-efficiency thick-film organic solar cells, and promote the commercialization of organic solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 2D GIWAXS images of embodiments of the present invention; wherein (a) is the 2D GIWAXS image of Comparative Example 1, (b) is the 2D GIWAXS image of Embodiment 1, and (c) is the 2D GIWAXS image of Embodiment 6.
[0015] Figure 2 1D line cutting diagrams of Comparative Example 1, Example 1, and Example 6; Figure 3 is the Urbach energy of Comparative Example 1, Example 1, and Example 6; Figure 4 It is the trap state density diagram of comparative example 1, embodiment 1, and embodiment 6; Figure 5 JV curves for Comparative Example 1, Example 1, and Example 6; Figure 6 EQE spectra of Comparative Example 1, Example 1, and Example 6; Figure 7 For Comparative Example 1, Example 1, Example 6 J ph -V eff curve; Figure 8 1 is the TPC curve of the organic solar cell of Comparative Example 1, Example 1 and Example 6; Fig. 9 TPV curves of Comparative Example 1, Example 1, and Example 6 Fig.10 For Comparative Example 1, Example 1, Example 6 J SC Dependence curve on light intensity; Fig.11 For Comparative Example 1, Example 1, Example 6 V OC Curve with light intensity; Fig.12 are photo-CELIV curves of Comparative Example 1, Example 1, and Example 6; Fig.13 1 and 2 are TPV curves of Comparative Example 2, Example 2, and Example 7; Fig.14 The electron mobility curves of Comparative Example 2, Example 2, and Example 7 are shown in FIG. DETAILED DESCRIPTION
[0016] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0017] This embodiment discloses an organic metal platinum complex, the specific structural formula of which is: .
[0018] The specific preparation method includes: Step 1, under nitrogen protection, add 2-bromothiazole, 2-(tributyltinyl)thiophene and a catalytic amount of tetrakistriphenylphosphine palladium into a flask. Then add anhydrous toluene, and stir the reaction mixture at 110°C for 24 hours. After cooling, pour the mixture into ultrapure water and extract with dichloromethane. The organic layer is dried over anhydrous MgSO4. The solvent is removed by evaporation under reduced pressure, and the crude product is purified by silica gel column chromatography to obtain compound 2-(thiophene-2-yl)thiazole (TTz).
[0019] Step 2, adding an aqueous solution of potassium tetrachloroplatinate to an acetic acid solution of TTz, and reflux heating under nitrogen; filtering out the precipitated solid of Pt(Ⅱ)-dichlorobridged dimer, washing with acetic acid and ethanol, and vacuum drying; reflux heating the dimer and sodium acetylacetonate in acetone, removing the solvent under reduced pressure, and purifying the complex by silica gel chromatography to obtain an organometallic platinum complex TTz-Pt.
[0020] The synthetic route is as follows:
[0021] The organic metal platinum complex TTz-Pt is used to prepare a thick film organic solar cell. The specific preparation method includes: Step 1, the ITO-coated glass substrate is cleaned by ultrasonic in detergent, deionized water, acetone and isopropanol for 15 minutes each, and blown dry with nitrogen; Step 2, subjecting the glass substrate obtained in step 1 to oxygen plasma treatment for 60 seconds, spin-coating a 30-nanometer-thick PEDOT:PSS on the glass substrate, baking at 150° C. for 15 minutes, and then transferring the substrate to a glove box filled with nitrogen; Step 3, spin coating an active layer with TTz-Pt on the substrate obtained in step 2, and performing a thermal annealing treatment; Step 4: Spin-coat PDINN solution on the substrate obtained in step 3, and form the top electrode by evaporating 100 nm of Ag. Define the active area of the device (4 mm2) by shadow mask.
[0022] The active layer can be selected from one of D18-Cl:L8-BO, PM6:L8-BO, and D18:L8-BO:IDIC.
[0023] Taking the active layer system D18-Cl:L8-BO as an example, different concentrations of TTz and TTz-Pt additives were added to the active layer to conduct performance tests. The results are shown in Table 1.
[0024] Table 1 D18-Cl:L8-BO OSCs (active layer thickness 100 nm) with different additives at AM 1.5 G100 mW cm -2 Photovoltaic parameters under illumination
[0025]
[0026] It can be seen from Table 1 that when the concentration of the additive TTz-Pt is 3%, the parameters of the organic solar cell are optimal, so the concentration of the additive in the embodiment and the comparative example is 3%.
[0027] Example 1 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a D18-Cl:L8-BO system, D18-Cl:L8-BO (1:1.2, weight ratio, D18-Cl concentration is 5 mg / ml) The active layer is dissolved in chloroform, 3 weight percent TTz-Pt of the donor is added, and spin-coated into a 100 nm thick film.
[0028] Example 2 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a D18-Cl:L8-BO system, the D18-Cl:L8-BO (1:1.2, weight ratio) active layer is dissolved in chloroform, 3 weight percent TTz-Pt of the donor is added, and spin-coated into a 300 nm thick film, wherein the concentration of D18-Cl is 8 mg / ml.
[0029] Example 3 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a PM6:L8-BO system, PM6:L8-BO (1:1.2, weight ratio, PM6 concentration of 8 mg / ml) The active layer is dissolved in chloroform, 3 weight percent TTz-Pt of the donor is added, and spin-coated into a 300 nm thick film.
[0030] Example 4 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses the D18:L8-BO:IDIC system, the D18:L8-BO:IDIC (1:1:0.2, weight ratio) active layer, 3 weight percent TTz-Pt of the donor is added, and spin-coated into a 100 nm thick film, wherein the concentration of D18 is 5 mg / ml.
[0031] Example 5 Based on the above-mentioned method for preparing thick-film organic solar cells, in this embodiment, the active layer uses the D18:L8-BO:IDIC system, the D18:L8-BO:IDIC (1:1:0.2, weight ratio) active layer, 3 weight percent TTz-Pt of the donor is added, and spin-coated into a 300 nm thick film, wherein the concentration of D18 is 8 mg / ml.
[0032] Example 6 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a D18-Cl:L8-BO system, D18-Cl:L8-BO (1:1.2, weight ratio, D18-Cl concentration is 5 mg / ml). The active layer is dissolved in chloroform, 3 weight percent TTz of the donor is added, and spin-coated into a 100 nm thick film.
[0033] Example 7 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a D18-Cl:L8-BO system, the D18-Cl:L8-BO (1:1.2, weight ratio) active layer is dissolved in chloroform, 3 weight percent of TTz as a donor is added, and spin-coated into a 300 nm thick film, wherein the concentration of D18-Cl is 8 mg / ml.
[0034] Example 8 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a PM6:L8-BO system, PM6:L8-BO (1:1.2, weight ratio, PM6 concentration of 8 mg / ml) active layer is dissolved in chloroform, 3 weight percent TTz of the donor is added, and spin-coated into a 300 nm thick film.
[0035] Example 9 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses the D18:L8-BO:IDIC system, the D18:L8-BO:IDIC (1:1:0.2, weight ratio) active layer, 3 weight percent TTz of the donor is added, and spin-coated into a 100 nm thick film, wherein the concentration of D18 is 5 mg / ml.
[0036] Example 10 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses the D18:L8-BO:IDIC system, the D18:L8-BO:IDIC (1:1:0.2, weight ratio) active layer, 3 weight percent TTz of the donor is added, and spin-coated into a 300 nm thick film, wherein the concentration of D18 is 8 mg / ml.
[0037] Comparative Example 1 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a D18-Cl:L8-BO system, D18-Cl:L8-BO (1:1.2, weight ratio, D18-Cl concentration of 5 mg / ml) active layer is dissolved in chloroform and spin-coated into a 100 nm thick film.
[0038] Comparative Example 2 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a D18-Cl:L8-BO system, and the D18-Cl:L8-BO (1:1.2, weight ratio) active layer is dissolved in chloroform and spin-coated into a 300 nm thick film, wherein the concentration of D18-Cl is 8 mg / ml.
[0039] Comparative Example 3 Based on the above-mentioned preparation method of thick-film organic solar cells, in this embodiment, the active layer uses a PM6:L8-BO system, and the PM6:L8-BO (1:1.2, weight ratio, PM6 concentration of 8 mg / ml) active layer is dissolved in chloroform and spin-coated into a 300 nm thick film.
[0040] Comparative Example 4 Based on the above-mentioned method for preparing thick-film organic solar cells, in this embodiment, the active layer uses a D18:L8-BO:IDIC system, a D18:L8-BO:IDIC (1:1:0.2, weight ratio) active layer, which is spin-coated into a 100 nm thick film, wherein the concentration of D18 is 5 mg / ml.
[0041] Comparative Example 5 Based on the above-mentioned method for preparing thick-film organic solar cells, in this embodiment, the active layer uses a D18:L8-BO:IDIC system, a D18:L8-BO:IDIC (1:1:0.2, weight ratio) active layer, which is spin-coated into a 300 nm thick film, wherein the concentration of D18 is 8 mg / ml.
[0042] Examples 1 to 10 and Comparative Examples 1 to 5 were tested, and the results are shown in the accompanying drawings and Tables 2-3 of the specification.
[0043] The effect of platinum additives on the molecular orientation and stacking behavior of the active layer was studied by GIWAXS. Figure 1 As shown, the 2D GIWAXS of Comparative Example 1, Example 1, and Example 6 show a π-π stacking (010) peak in the OOP direction, which means that the preferred out-of-plane molecular orientation in the hybrid film that is beneficial to charge transport can still be well maintained after treatment with different additives. The line cutting profiles of the three films are shown in Figure 2 Comparative Example 1, Example 1, and Example 6 exhibit 010 peaks in the OOP direction, which are located at qz=1.720, 1.732, and 1.729 Å, respectively. -1 , the π-π stacking distances are 3.650, 3.627, and 3.634 Å, respectively. In addition, the calculated CCLs of the 010 peak are 18.97, 28.13, and 25.93 Å for Comparative Example 1, Example 1, and Example 6, respectively. The smaller π-π stacking distance and larger CCL indicate that the addition of TTz-Pt results in tighter molecular stacking and higher crystallinity in the D18-Cl:L8-BO film, which is beneficial to promote charge transport and thus improve device performance.
[0044] Taking into account the crystallinity differences among Comparative Example 1, Example 1, and Example 6, the Urbach energy (E U ) to study energy disorder. Figure 3 As shown, the calculated E U The values are 22.29 meV, 20.89 meV and 21.15 meV in Comparative Example 1, Example 1 and Example 6 respectively. The reduced energy disorder in Example 1 is consistent with the improved crystallinity, which can improve the charge transport process. In addition, the trap state density (Nt) is also related to the carrier transport behavior, such as Figure 4 The calculated Nt values are 5.23×10 16 , 3.97×10 16 and 4.67×10 16 cm -3 The reduced Nt in Example 1 suppressed charge recombination and improved exciton diffusion and charge transport processes. These results suggest that the addition of TTz-Pt enhances device performance. Combining these advantages, the addition of TTz-Pt improves crystallinity, reduces energy disorder and trap state density, and contributes to a larger exciton diffusion coefficient, thereby extending the exciton diffusion length.
[0045] The performance of organic solar cells based on D18-Cl:L8-BO with TTz-Pt additive was tested. The current density-voltage (JV) curve is shown in Figure 5 As shown in Table 2, combined with the photovoltaic parameters, comparative example 1 achieved a power conversion efficiency of 18.18%, J SC 26.05 mA cm-2 , V OC The power conversion efficiency of Example 6 is 0.916 V and the FF is 76.2%. SC 26.23 mA cm -2 , V OC The power conversion efficiency of Example 1 was 19.63%, and the J SC 26.61 mA cm -2 , V OC It is 0.929 V and the FF is 79.4%.
[0046] The external quantum efficiency (EQE) spectrum of the best device is shown in Figure 6 Example 1 shows a higher EQE response in the 500-800 nm region than Comparative Example 1 and Example 6, which indicates a more efficient conversion of photons to carriers, which brings enhanced J to Example 1. SC In addition, the EQE curve integral J of Comparative Example 1, Example 1 and Example 6 SC 25.13, 25.70 and 25.51 mA cm, respectively. -2 , and J measured by JV curve SC Consistent.
[0047] In order to study the exciton dissociation probability (P diss ), the photocurrent density (J ph ) and the effective voltage (V eff ) curve. Figure 7 As shown, P of Example 1 diss The value is 99.49%, which is higher than that of Comparative Example 1 (96.50%) and Example 6 (97.89%). coll ) increased from 81.34% in Comparative Example 1 to 84.17% in Example 1 and 83.13% in Example 6. The higher P diss and P coll This suggests more efficient exciton dissociation and charge collection, which can be attributed to the extension of the exciton diffusion length.
[0048] To investigate the effect of TTz-Pt additives on charge extraction and charge carrier lifetime in organic solar cells, transient photocurrent (TPC) and transient photovoltage (TPV) measurements were performed. Figure 8-9As shown, the charge extraction times of Comparative Example 1, Example 1 and Example 6 are 0.52, 0.35 and 0.42 μs, respectively. In addition, the charge carrier lifetimes fitted from the TPV curve are 2.57, 3.48 and 3.31 μs, respectively. Compared with Comparative Example 1, the additive-treated organic solar cells show a faster charge extraction process and a longer charge carrier lifetime, especially Example 1, which is consistent with J SC The same improvement as FF. SC and light intensity (P light ) measurements are used to study the effect of TTz-Pt on the charge recombination mechanism of organic solar cells. SC With P light The relationship between them is described as J SC ∝P light α( Fig.10 ), the α values of Comparative Example 1, Example 1 and Example 6 are 0.96, 0.97 and 0.96 respectively, indicating that the bimolecular recombination in all three organic solar cells is weak. In addition, by measuring the V OC As P light Function to study trap-assisted recombination. Fig.11 As shown, the n value of Example 1 is 1.01, which is less than 1.16 of Comparative Example 1 and 1.05 of Example 6, indicating that trap-assisted recombination is suppressed in Example 1. The photoinduced charge carrier extraction (photo-CELIV) under linearly increasing voltage revealed the charge transport behavior of the active layer with and without additive treatment. Fig.12 As shown, the carrier mobility of Comparative Example 1, Example 1, and Example 6 are 1.61×10 -4 , 2.22×10 -4 and 2.05×10 -4 cm 2 V -1 s -1 The improved charge transport properties may explain the enhanced J SC and FF values.
[0049] The extended exciton diffusion length will allow more excitons to diffuse to the D / A interface, providing great potential for the manufacture of high-efficiency thick-film organic solar cells. The longest exciton diffusion length was obtained in Example 1 through TPV experiments, which was 38.3 nanometers ( Figure 13-14 ), which is larger than the exciton diffusion length of Comparative Example 1 (18.3 nm) and Example 6 (23.7 nm). Therefore, the 300 nm thick film in Example 2 exhibits a higher PCE of 18.63% than that of Comparative Example 1 (17.23%) and Example 6 (17.71%).
[0050] In order to study the universality of TTz-Pt in improving the photovoltaic performance of thin-film and thick-film devices, representative active layer systems including PM6:L8-BO and D18:L8-BO:IDIC were applied, as shown in Table 3. The active layer system formula is:
[0051]
[0052] A power conversion efficiency of 20.12% was achieved in Example 4. Thanks to the superior thickness insensitivity of the TTz-Pt additive treatment, a power conversion efficiency of 18.84% was achieved in Example 5, which is higher than the power conversion efficiency of 300 nm thick organic solar cells in the prior art. These results indicate that by introducing an organometallic platinum complex (TTz-Pt) as a solid additive, a simple and universal method was developed to achieve the preparation of high-efficiency thick-film organic solar cells by extending the exciton diffusion length.
[0053] Table 2 Photovoltaic parameters of D18-Cl:L8-BO OSCs with different active layer thicknesses under different additive treatments
[0054]
[0055] Table 3 Photovoltaic parameters of OSCs with various active layers processed with different additives
[0056] This embodiment also discloses an organic metal palladium complex, the structural formula of which is:
[0057] The specific preparation method includes: Step 1, under nitrogen protection, add 2-bromothiazole, 2-(tributyltinyl)thiophene and a catalytic amount of tetrakistriphenylphosphine palladium into a flask. Then add anhydrous toluene, and stir the reaction mixture at 110°C for 24 hours. After cooling, pour the mixture into ultrapure water and extract with dichloromethane. The organic layer is dried over anhydrous MgSO4. The solvent is removed by evaporation under reduced pressure, and the crude product is purified by silica gel column chromatography to obtain compound 2-(thiophene-2-yl)thiazole (TTz).
[0058] Step 2, adding an aqueous solution of potassium tetrachloropalladate to an acetic acid solution of TTz, and reflux heating under nitrogen; filtering out the precipitated solid of Pd(II)-dichlorobridged dimer, washing with acetic acid and ethanol, and vacuum drying; reflux heating the dimer and sodium acetylacetonate in acetone, removing the solvent under reduced pressure, and purifying the complex by silica gel chromatography to obtain an organometallic platinum complex TTz-Pd.
[0059] In addition, other coordinated metals (II) Cu, Fe, Ni, Co, and Zn can also be arranged in a planar manner with the surrounding ligands to form a planar structure, thereby achieving properties similar to TTz-Pt. This planar structure allows these complexes to have specific stereochemical characteristics in chemical reactions, which is very important in many optoelectronic processes. Therefore, metal complexes formed by other coordinated metals can achieve excellent performance in thick-film organic solar cells.
[0060] The above embodiments are only exemplary embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
Claims
1. An organometallic complex, characterized in that The structural formula of the organometallic complex is: ; Wherein, the metal X is selected from any one of Pt, Pd, Cu, Fe, Ni, Co, and Zn; The R unit is selected from any one of a linear or branched alkyl group having 1 to 3 carbon atoms.
2. A method for preparing an organometallic complex, characterized in that: For preparing the organometallic complex as claimed in claim 1, specifically comprising: Step 1, under nitrogen protection, 2-bromothiazole, 2-(tributyltinyl)thiophene or (thieno[3,2-b]thiophene-2-yl)tributyltin and a catalytic amount of tetrakistriphenylphosphine palladium are added to a flask; anhydrous toluene is added, and the reaction mixture is stirred at 110° C. for 24 hours; after cooling, the mixture is poured into ultrapure water and extracted with dichloromethane; the organic layer is dried over anhydrous MgSO4; the solvent is removed by evaporation under reduced pressure, and the crude product is purified by silica gel column chromatography to obtain compound 2-(thiophene-2-yl)thiazole or 2-(thieno[3,2-b]thiophene-2-yl)thiazole; Step 2, adding an aqueous solution of K2XCl4 to the acetic acid solution of 2-(thiophene-2-yl)thiazole or 2-(thieno[3,2-b]thiophene-2-yl)thiazole obtained in step 1, and reflux heating under nitrogen; filtering to obtain a dimer, washing with acetic acid and ethanol, and vacuum drying; reflux heating the dimer and sodium acetylacetonate in acetone, removing the solvent under reduced pressure, and purifying the complex by silica gel chromatography to obtain an organometallic complex.
3. Use of the organic metal complex as claimed in claim 1 in the preparation of thick-film organic solar cells.
4. The use according to claim 3, characterized in that: The specific preparation method of thick film organic solar cells includes: Step 1, the ITO-coated glass substrate is cleaned by ultrasonic in detergent, deionized water, acetone and isopropanol, and blown dry with nitrogen; Step 2, treating the glass substrate obtained in step 1 with oxygen plasma, spin-coating PEDOT:PSS on the glass substrate, and transferring the substrate to a glove box filled with nitrogen after drying; Step 3, spin coating an active layer with an organic metal complex on the substrate obtained in step 2, and performing a thermal annealing treatment; Step 4: Spin-coat the PDINN solution on the substrate obtained in step 3, and form a top electrode by evaporating 100 nanometers of Ag.
5. The use according to claim 4, characterized in that: The amount of the organic metal complex added in step 3 is 1.5%-4.5% of the body weight.
6. The use according to claim 4, characterized in that: The active layer is specifically one of D18-Cl:L8-BO, PM6:L8-BO, and D18:L8-BO:IDIC.
7. The use according to claim 4, characterized in that: The thickness of the active layer is 100-300 nanometers.
Citation Information
Patent Citations
Epoxy platinum complex as well as preparation method and application thereof
CN112500437A
Platinum-containing metal organic conjugated polymer, preparation method thereof and thermoelectric device
CN115584016A
Organic solar cell, active layer thereof and preparation method of active layer
CN117835787A
Application of deuterated dihalogenated benzene solid additive in organic solar cell
CN118829240A
Application of solid additive in organic solar cell and cell preparation method
CN118890906A